2020
DOI: 10.1177/2045125320932452
|View full text |Cite
|
Sign up to set email alerts
|

How user knowledge of psychotropic drug withdrawal resulted in the development of person-specific tapering medication

Abstract: Coming off psychotropic drugs can cause physical as well as mental withdrawal, resulting in failed withdrawal attempts and unnecessary long-term drug use. The first reports about withdrawal appeared in the 1950s, but although patients have been complaining about psychotropic withdrawal problems for decades, the first tentative acknowledgement by psychiatry only came in 1997 with the introduction of the ‘antidepressant-discontinuation syndrome’. It was not until 2019 that the UK Royal College of Psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
0
41
0
2
Order By: Relevance
“…28,51 This suggests that the NICE guidance on how to discontinue antidepressants needs to be updated, and new guidance on Safe Prescribing and Withdrawal from prescribed drugs associated with dependence will hopefully contribute to best practice in this area. 52 Overall, there has been scant attention paid to the issue of antidepressant tapering previously in the academic literature, 48,[53][54][55][56] which has been focused primarily on starting medication. 57 The ANTLER and REDUCE trials are ongoing, but further trials will be required in order to provide detailed advice to GPs on how to taper medications.…”
Section: Lack Of Access To Effective Management/ Informed Medical Ovementioning
confidence: 99%
“…28,51 This suggests that the NICE guidance on how to discontinue antidepressants needs to be updated, and new guidance on Safe Prescribing and Withdrawal from prescribed drugs associated with dependence will hopefully contribute to best practice in this area. 52 Overall, there has been scant attention paid to the issue of antidepressant tapering previously in the academic literature, 48,[53][54][55][56] which has been focused primarily on starting medication. 57 The ANTLER and REDUCE trials are ongoing, but further trials will be required in order to provide detailed advice to GPs on how to taper medications.…”
Section: Lack Of Access To Effective Management/ Informed Medical Ovementioning
confidence: 99%
“…Dose and day information printed on each pouch allow patients to precisely record and monitor the progress of their reduction. 8,10 In a previous study, we reported that 71% of patients using a taperingstrip, mainly for venlafaxine and paroxetine, were able to come off their drug in the short term, reporting the outcome after a 2-3 month course with taperingstrips, using a median of two 28-day taperingstrips. 11 Here, we report on the longer term, 1-5 year outcome of antidepressant taperingstrips in a sample of 483 users of psychotropic drugs in the Netherlands, of whom 408 used an antidepressant.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in response to users of antidepressant medication trying to come off, the not-for-profit organisation Cinderella Therapeutics in the Netherlands oversaw the development of personal taperingstrips for hyperbolic reduction of antidepressant medication in those suffering withdrawal or deemed at risk. 8 , 10 A taperingstrip consists of antidepressant medication, packaged in a roll or strip of small daily pouches. Each pouch is numbered and has the same, or slightly lower, dose than the one before it.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations